Soil microbial communities changed with a continuously monocropped processing tomato system - Yalong Kang; Feng Jing; Wenqinq Sun; Jianguo Liu; Guiying Jiang (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2018)
To reveal the regulatory mechanisms underlying the productivity of long-term continuous cropping of processing tomato, a multi-year study was carried out to understand the effects of long-term continuous cropping on the community structures of the root zone microbes. Soil samples collected from continuous cropping of processing tomato after 3, 5 and 7 years were used for this study. Results showed that soil microbial biomass C (SMBC), N (SMBN) and microbial quotient (qMB) significantly decreased with longer cropping. After seven years of continuous cropping, the SMBC and SMBN contents, and qMB respectively significantly decreased by 52.3%, 78.8% and 48.2% (p < 0.01). In contrast, soil microbial biomass P (SMBP) increased during the first three years of continuous cropping, peaking to up to 1.6 times higher than that of the control, which also declined in the succeeding years. Continuous cropping significantly increased the PLFA of fungi, whereas the opposite trend was observed for bacteria, total PLFAs biomass, and the ratios of bacteria and fungi. The PLFA of actinomycetes have no change throughout. This suggests that fungi were better adapted to nutrient poor conditions than bacteria. Microbial diversity indices reached the highest after three years of continuous cropping, with the lowest observed after seven years. This indicated that microbial community diversity and uniformity decreased with increasing number of planting years. Furthermore, our results revealed that the microbial community structure in processing tomato soils changed with extended cropping, resulting to a decline in soil microbial biomass, which may be both a cause and a reflection of the poor soil quality.